Outcomes with single agent LIPO-DOX in platinum-resistant ovarian and fallopian tube cancers and primary peritoneal adenocarcinoma - Chiang Mai University Hospital experience - Suprasert P. (Asian Pacific Organization for Cancer Prevention, 2014)
Background: Single pegylated liposomal doxorubicin (PLD) is commonly used as a salvage treatment in platinum-resistant ovarian cancer, fallopian tube cancer and primary peritoneal adenocarcinoma (PPA) with a satisfactory outcome. However, the data for second generation PLD administered in this setting are still limited. We conducted a retrospective study to evaluate the outcome of patients who received single-agent second generation PLD (LIPO-DOX) after the development of clinical platinum resistance. The study period was between March 2008 and March 2013. LIPO-DOX was administered intravenously 40 mg/m2 every 28 days until disease progression, but for not more than six cycles. The response rate was evaluated using the Gynecologic Cancer Intergroup (GCIG) criteria while the toxicity was evaluated according to WHO criteria. Twenty-nine patients met the inclusion criteria in the study period with an overall response rate of 13.8%. The median progression free survival and overall survival were three and eleven months, respectively. With the total of 96 cycles of chemotherapy, the patients developed grades 3 and 4 hematologic toxicity as follows: anemia, 0%, leukopenia, 9.6%, neutropenia, 32.3% and thrombocytopenia, 0%. In conclusion, the single agent second generation PLD demonstrated modest efficacy in patients with platinum-resistant ovarian cancer, fallopian tube cancer and PPA without serious toxicity.